PERAN MAHASISWA KKN INTERNASIONAL DALAM EDUKASI KURIKULUM NASIONAL PADA KOMUNITAS DIASPORA INDONESIA DI MADINAH - Rakha Hermawan; Rahimah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This article aims to analyze the role of students participating in the International Community Service Program (KKN) at the University of Muhammadiyah North Sumatra (UMSU) in educating the Indonesian diaspora community in Medina, Saudi Arabia, about the Indonesian National Curriculum. This study was motivated by the diaspora community’s limited access to formal educational institutions based on the Indonesian National Curriculum, thereby necessitating an alternative form of education through community service activities involving students. The study employed a qualitative approach using descriptive methods. Data were collected through interviews, observations, and documentation of the activities of International KKN students and the Indonesian diaspora community in Madinah. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that UMSU International Community Service Program (KKN) students play three main roles: educators, learning facilitators, and cultural mediators. As educators, the students deliver the Indonesian National Curriculum while instilling national values in children of the diaspora. As learning facilitators, they create active and adaptive learning processes through various teaching methods and media tailored to the learners’ needs. Meanwhile, as cultural mediators, the students strive to connect national educational values with the sociocultural context of the diaspora community in Madinah. The learning process is implemented through a service-learning approach that enables the integration of academic activities and community service. Despite facing challenges such as limited educational resources, time constraints, and differences in students’ language proficiency, this program has received a positive response from the diaspora community. This study concludes that the International Community Service Program (KKN) contributes to strengthening national identity, enhancing understanding of Indonesian culture, and supporting the continuity of national education for the younger generation of the Indonesian diaspora abroad.